Comparison of MPV and High Sensitive CRP Levels between Patients with and without Diabetic Microvascular Complication - SÜNBÜL, MURAT (GALENOS YAYINCILIK, 2015)
Aim: Diabetes is an important cause of mortality and morbidity affecting especially individuals with its complications. We aimed to draw attention to the fact that MPV and hsCRP can be evaluated as warning parameters in terms of development of the complications of diabetes. Methods: 139 patients who were followed up in the diabetes outpatient clinics in Haseki Training and Research Hospital between years 2005-2009 were included in this study. The study group consisted of 83 patients (49 females, 34 males) with microvascular complications. The control group was composed of 56 patients (32 females, 24 males) without microvascular complications. The levels of creatinine, HbA1c, hemogram, hsCRP, albumin, triglyceride and total-HDL-LDL cholesterol were measured in all patients. Age, diabetes age, body mass index and waist circumference were also evaluated. Information about microvascular complications (fundoscopic examination or 24-hour urine investigation) was obtained from the patient files. Results: Age, age of onset of diabetes, hemoglobin, hematocrit, creatinine and HbA1c values in the study group were significantly higher compared to that in the control group. In addition, the albumin values in the study group were lower than in the control group. Conclusion: In diabetic patients, MPV and hsCRP levels increase but a direct relationship of this increase with microvascular complications was not determined. However, these parameters can be an indication of the risk of retinopathy-nephropathy development in diabetic patients, because of their relationship with poor blood glucose regulation.
Keywords: Diabetes; inflammation; MPV; HsCRP; microvascular complication